THE EFFICIENCY OF THE CONTAINER TERMINALS IN ADRIATIC: AN IMPROVED DATA ENVELOPMENT ANALYSIS - Evelin Krmac; Mozhgan Mansouri Kaleibar (Operational Research in Engineering Sciences: Theory and Applications)
Ports have a very important role in global trade networks and serve as a critical nodes for the transport of goods around the world, while their container terminals act as an important engines for local and regional development. However, port operations present challenges and complexities that require optimal management and strategic planning. This study focuses on evaluating the sustainability-based efficiency of the Adriatic container terminals using the Data Envelopment Analysis (DEA) method over the last three years. The proposed model ND-SBM-UO was developed for the case of uncontrollable inputs (ND) and undesirable outputs (UO). Indicators were defined to evaluate the efficiency of container terminals when there is no access to certain data. Indicators were also defined that were missing in previous studies, such as the degree of connectivity and the level of equipment of the terminals are also defined. In this way, efficient and inefficient container terminals, and the causes of inefficiency at individual container terminals are defined. The proposed model is used to identify efficient and inefficient terminals and their efficiency scores. In addition, this study will search for the reference container terminals and determine the causes of inefficiency of each container terminal based on the reference container terminals and returns to scale. The results of this study could be helpful when improving the efficiency and performance of the container terminals. This work will be of keen interest to research community and policy makers in the transport sector, exporters/importers of companies, and port authorities.